Spontaneous Versus Directed Pushing Technique: Maternal and Neonatal Outcomes: A Comparative Study in Northern Upper Egypt (International Journal of Studies in Nursing, 2021)
Background: Maternal pushing during the 2nd stage of labor is indispensable and important contributor to the involuntary expulsive force developed by uterine contraction results to influence on the mother and fetus. Aim: the study was conducted to compare spontaneous versus Valsalva (directed) pushing techniques at the second stage of labor on maternal and fetal outcomes. Methods: Setting: Delivery Unit of El-Fayoum General and University Hospitals. Design: A quasi-experimental comparative study. Subjects: A purposive sample of a total of 100 primiparous women; 50 in the Valsalva (directed) pushing group & 50 in the spontaneous pushing group. Tools: four tools were used; structured interviewing questionnaire sheet, Apgar score, Visual analog scale, and women satisfaction questionnaire. Results: The duration of the second stage of labor was shorter (5-10 min) in a spontaneous pushing (54.0%) group compared to the direct pushing group (2.0%). Oxygen wasn't used at all in spontaneous pushing group compared to 74.0% of directed pushing group. Postpartum hemorrhage was too little in spontaneous pushing group (96.0%) compared to 36.0% of the directed pushing group. Also, all women in the spontaneous pushing group experienced mild perineal pain compared to 32.0% in the directed pushing group (p